2012
DOI: 10.1007/s10103-012-1079-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse reflectance spectroscopy as a tool to measure the absorption coefficient in skin: system calibration

Abstract: An individualised laser skin treatment may enhance the treatment and reduces risks and side-effects. The optical properties (absorption and scattering coefficients) are important parameters in the propagation of laser light in skin tissue. The differences in the melanin content of different skin phototypes influence the absorption of the light. The absorption coefficient at the treatment wavelength for an individual can be determined by diffuse reflectance spectroscopy, using a probe containing seven fibres. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…VISIA ® only uses the absorption of the UV light by the epidermal melanin to detect the UV spot whereas melanin is an optically dense material which absorbs radiation in the visible wavelength range. 13 The traditional methods of measuring skin texture include mechanical detection method 14 and subsequent silica gel laminating method. 15 The pores are slightly reduced with the increase of age, but the result was not statistically significant.…”
Section: Age Correlationsmentioning
confidence: 99%
“…VISIA ® only uses the absorption of the UV light by the epidermal melanin to detect the UV spot whereas melanin is an optically dense material which absorbs radiation in the visible wavelength range. 13 The traditional methods of measuring skin texture include mechanical detection method 14 and subsequent silica gel laminating method. 15 The pores are slightly reduced with the increase of age, but the result was not statistically significant.…”
Section: Age Correlationsmentioning
confidence: 99%
“…The probe calibration procedure is described in an earlier article . The probe was calibrated on a set of liquid phantoms.…”
Section: Methodsmentioning
confidence: 99%
“…2 : Rp(λ)=μs '(λ)k1+k2μa(λ) where k 1 and k 2 are calibration parameters that depend on the probe geometry and the experimental setup. These parameters were calculated from the phantoms as k 2 = 0.016312 and k 2 = 0.019144 . Equation 2 is based on the model described by Zonios that assumes a single semi‐infinite, homogeneous medium or layer.…”
Section: Methodsmentioning
confidence: 99%
“…Raw DRS data is given in terms of reflectance, that is, the percentage of light recovered from a detection fiber to light delivered by a source fiber. Studies have shown that volume-averaged optical properties, such as reduced scattering coefficient (μ s ′) and absorption coefficient (μ a ) can be determined from in vivo samples34384041424344454647. It should be noted that these extracted values are based on the delivery and collection of light throughout an often inhomogeneous layered media, such as tissue, and extracted optical properties thus represent volume averaged, rather than axially resolved, values.…”
mentioning
confidence: 99%
“…Several in vivo DRS studies have extracted other clinically relevant optical parameters including blood volume fraction, hemoglobin concentration, oxygen saturation, mean blood vessel diameter, nicotinamide adenine dinucleotide (NADH) concentration, and tissue thickness343536374849505152. Furthermore, DRS is an appealing non-invasive screening technique because it is sensitive to optical changes beneath the apical tissue layer3334353637383940414243444546474849505152. However, a drawback of DRS is inability to spatially resolve tissue architecture.…”
mentioning
confidence: 99%